Unsteady MHD Flow Past an Impulsively Started Inclined oscillating Plate with Variable Temperature and Mass Diffusion in the presence of Hall current - U. S. Rajput; Gaurav Kumar (International Journal of Applied Methods in Electronics and Computers, 2017)
Unsteady MHD flow past an impulsively started inclined oscillating plate with variable temperature and mass diffusion in the presence of Hall current is studied here. The fluid considered is gray, absorbing-emitting radiation but a non-scattering medium. The Governing equations involved in the present analysis are solved by the Laplace-transform technique. The velocity profile is discussed with the help of graphs drawn for different parameters like Grashof number, mass Grashof Number, Prandtl number, Hall current parameter, phase angle, the magnetic field parameter and Schmidt number, and the numerical values of skin-friction have been tabulated.